La interiorización de valores y la convivencia escolar. - Borja Romero, Rafael Abelardo (2018)
This research deals with the theme: the internalization of values and school coexistence, this research project seeks to find relevant information about the problem: The deficient practice of values affect school coexistence whose general objective is to diagnose the internalization of values and coexistence school, through the application of different strategies, workshops and talks that originate good social and behavioral relationships among students of the 5th grader students at Unidad Educativa "Mariscal Antonio José de Sucre". For this purpose, a scientific, analytical and statistical research methodology was used to gather valuable information from various bibliographical sources to support the problem, instruments and techniques were also used to collect information and prepare statistical data to analyze the need and feasibility of the proposal. Bearing in mind the need to strengthen values as fundamental axes for good school coexistence, since currently the values are disappearing and there is no normal development in the formation of the human being. Consequently, some issues appear within the social context being one of the main fundamental demands that the human being has, which will serve as an ideal support in the normal development of people and their relationship with others. Taking into account that the values educate open-minded people focused on fulfilling with and enforcing norms that establish a normal development of people, as a reference the behavioral model is taken which focuses on the behavior modification during childhood and adolescence, placing values as fundamental pillars in the formation of the human being, enhancing good behaviors that will be put into practice throughout their training as integrated people able to relate to their peers solving problems that arise in this new society.